Use of lucuma seed episperm as activated charcoal - Suárez Ramos, Diego (2022)
Generation of waste is one of the main problems faced by the agroindustry due to the inadequate management and treatment given. Therefore, it is vital to look for alternatives for the use of waste that can generate added value. The aim of the research was to determine the competence of the episperm lucuma seed (ELS) in the elaboration of activated carbon (AC).  was used as activating agent at two impregnation ratios (0.2 and 0.4g/g episperm) at three temperatures (600, 700 and 800 °C) and three carbonization times (15, 30 and 45 min). 18 treatments were obtained. Methylene blue (MB) dye was used as adsorbate. Chemical kinetics, adsorption capacity and adsorption isotherms of the MB-AC system were studied. The adsorption surface area was determined by the BET isotherm with gaseous nitrogen, the functional groups and morphology of CA were characterized by infrared spectroscopy and scanning electron microscopy, respectively. The results show a kinetics of the pseudo second order, while the adsorption behavior in relation to the MB concentration corresponds to a sigmoidal isotherm which fits the Frumking-Fowler-Guggenheim (FFG) isotherm model. The treatment that presented the highest percentage of adsorption (94.5 %) was AC0.4_600°C30’, obtaining a surface area of 648 m²/g. It is concluded that ELS is suitable for use as activated carbon.